DevOps Delivers. - FORSGREN, NICOLE (Communications of the ACM, 2018)
An introduction is presented to a special section on the software development and delivery methodology DevOps, noting articles on objections to continuous delivery, the role of culture in technology transformation, and data capture in relation to software development and delivery.